Natural products targeting ubiquitination to combat kidney fibrosis - Lianhua Li; Xinhui Huang; Yao Chen; Jibin Liu; Yuhang Qiao; Wenyu Fan; Peiqing Zhang; Xiaoming Yan; Ming Chen (Future Journal of Pharmaceutical Sciences)
Abstract Background Kidney fibrosis is a crucial component that contributes to end-stage renal disease and is the inevitable last pathological process in many progressive chronic kidney diseases (CKD). Ubiquitination, one of the most refined and widespread reversible post-translational modifications, plays a significant role in the development of renal fibrosis through its regulation and deubiquitination processes. Main body of the abstract Recent studies have shown that ubiquitination and deubiquitination represent promising intervention targets against renal fibrosis, with numerous natural products intervening in renal fibrosis by regulating the processes of ubiquitination and signal pathways such as transforming growth factor-β1/Smads (TGF-β1/Smads), Wnt/β-catenin, Janus kinase/signal transducer and activator of transcription/suppressor of cytokine signaling (JAK/STAT/SCOS), and nuclear factor erythroid-derived 2-like 2 (Nrf2), and then link. Conclusion Herein, we summarize the processes of ubiquitination and deubiquitination and introduce the interactions between ubiquitination and natural products. This is conducive to the development of new candidate drugs that intervene in renal fibrosis through the regulation of ubiquitination, representing a promising strategy to combat renal fibrosis with natural products. Graphical abstract